Allowance for more realistic trajectories of plasma electrons in the Stark broadening of hydrogenlike spectral lines. (16th March 2018) - Sanders, P; Oks, E
Abstract: In the Conventional Theory (CT) of the electron broadening of hydrogenlike spectral lines in plasmas, the perturbing electrons are considered moving along hyperbolic trajectories in the Coulomb field of the effective charge Z − 1 (in atomic units), where Z is the nuclear charge of the radiating ion. Thus, the CT assumed that the motion of the perturbing electron can be described in frames of a two-body problem, one particle being the perturbing electron and the other 'particle' being the charge Z − 1. However, in reality it is a three-body problem, involving the perturbing electron, the nucleus, and the bound electron, so that trajectories of the perturbing electrons should be more complicated. In the present paper we take this into account via the standard analytical method of separating rapid and slow subsystems by using the fact that the characteristic frequency of the motion of the bound electron around the nucleus is much higher than the characteristic frequency of the motion of the perturbing electron around the radiating ion. By applying this method we obtain more accurate analytical results for the electron broadening operator than in the CT. We show by examples of the electron broadening of the Lyman lines of He II that the allowance for this effect increases with the electron density Ne, becomes significant already at Ne ∼ 10 17 cm −3 and very significant at higher densities. We also briefly discuss a paper by Baryshnikov and Lisitsa ( Sov. Phys. JETP 53 (1981) 471) where the fundamental symmetry of the effective potential for this problem was used in a different way.